Peningkatan Penggunaan Microsoft Office Untuk Pengolahan Data Bagi Yayasan Kopia Raya Insani - Lala Nilawati; Indah Ariyati; Noer Hikmah; Herlambang Brawijaya (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2023)
Utilization of Information and Communication Technology, one of which is a computer, is increasingly being used day by day. Various applications on the computer make it very easy for users, especially to complete daily tasks. The Kopia Insani Foundation in the South Jakarta area has not experienced the maximum use of computers. Weaknesses in data processing at the Kopia Insani Foundation can be seen in managing foundation data, due to a lack of technological knowledge and no use of computers in managing the Foundation, and a lack of human resources in operating computers. This community service activity is carried out in the form of training to improve computer operation, as a form of understanding technology and information within an organization or company. The results of this training activity are to improve the operation of computer programs, namely Microsoft Office applications, in the form of increasing the skills of trainees towards more detailed knowledge about using Microsoft Office, which can be used in data processing accompanied by various case exercises.